2022
DOI: 10.1371/journal.pone.0273435
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to anti-retroviral therapy adherence among adolescents aged 10 to 19 years living with HIV in sub-Saharan Africa: A mixed-methods systematic review protocol

Abstract: Background Antiretroviral therapy (ART) adherence is fundamental in achieving viral load suppression and consequently attaining positive health outcomes among people living with HIV. However, ART adherence is sub-optimum among adolescents living with HIV (ALHIV) thus the high AIDS-related mortality even after World Health Organization (WHO) revised HIV treatment eligibility guidelines in 2010, 2013 and 2016. Consolidated trends of barriers to ART adherence among ALHIV aged 10 to 19 years in sub-Saharan countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…However, the findings reported lower VLS rates compared to 2012 findings where VLS was at 84% in low-and middle-income countries yet was in consistent with findings of a systematic review reporting 59% in SSA [101,102] . Secondly, loss to follow up in our review was 17% (95% CI [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which is lower to findings of a study conducted in 34 countries under the International epidemiology Database to Evaluate AIDS (IeDEA) where LTFU was reported to be 30% in 2018 [105]. Loss to follow up rate in this review indicate improvement when compared to studies conducted in 2007 in SSA where LTFU was 51% [106].…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 54%
See 1 more Smart Citation
“…However, the findings reported lower VLS rates compared to 2012 findings where VLS was at 84% in low-and middle-income countries yet was in consistent with findings of a systematic review reporting 59% in SSA [101,102] . Secondly, loss to follow up in our review was 17% (95% CI [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which is lower to findings of a study conducted in 34 countries under the International epidemiology Database to Evaluate AIDS (IeDEA) where LTFU was reported to be 30% in 2018 [105]. Loss to follow up rate in this review indicate improvement when compared to studies conducted in 2007 in SSA where LTFU was 51% [106].…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 54%
“…The systematic review is registered with PROSPERO (Registration: CRD42021284891) [22]. The results are reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA statement) [23], and the Enhancing Transparency in Reporting the synthesis of Qualitative research (ENTREQ) recommendations [24].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it complemented and enriched its analysis based on articles published in journals indexed in the JCR-WoS, with three articles on the same topic that were already included in a previous review that did not consider the first bibliometric technique indicated in the present methodological design. In this way, it was possible to incorporate six articles that covered five original empirical studies on telesupervision and that were evaluated with a tool (MMAT) that has been applied in several reviews related to health and mental health [ 72 , 73 , 74 ] among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, The Joint United Nations Program Against HIV/AIDS (UNAIDS) estimates, indicated that the global VLS in the sub-population was at 46% during the same year. A recent systematic review in SSA, reported a 55% VLS among the ALHIV and 65% adherence [4]. Similarly, In Uganda,.…”
Section: Introductionmentioning
confidence: 94%
“…Barriers to optimal VLS identi ed include; di culties nding transport money, unfriendly health settings, drug stock outs, prolonged waiting time, unfavorable school timetable, non-disclosure of HIV status and drug side effects [4][5][6][7][8][9][10]. Conversely, identi ed enablers include reliable stock-levels of drugs in the facilities, good attitude of health-workers, availability of transport money, social/family support, and positive peer in uence [4,7,8]. To counteract the barriers while enhancing the enablers, interventions implemented in different settings across Uganda.…”
Section: Introductionmentioning
confidence: 99%